2008
DOI: 10.1021/la703098g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of F-Doped Flower-like TiO2 Nanostructures with High Photoelectrochemical Activity

Abstract: We report on a novel and facile approach for the direct growth of F-doped flower-like TiO(2) nanostructures on the surface of Ti in HF solutions under low-temperature hydrothermal conditions. The influence of the experimental parameters such as temperature, reaction duration, and the HF concentration on the morphology and photoelectrocatalytic activity of the formed F-doped flower-like TiO(2) nanostructures was systematically studied. The presence of HF and the reaction time play an important role in the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
189
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(194 citation statements)
references
References 24 publications
5
189
0
Order By: Relevance
“…Such dramatic compositional changes were due to rapid dissolution of titanium (Ti) substrate as shown in Equation (1). [37] Ti þ 6HF ! H 2 TiF 6 þ 2 H 2 " ð 1Þ…”
Section: Resultsmentioning
confidence: 99%
“…Such dramatic compositional changes were due to rapid dissolution of titanium (Ti) substrate as shown in Equation (1). [37] Ti þ 6HF ! H 2 TiF 6 þ 2 H 2 " ð 1Þ…”
Section: Resultsmentioning
confidence: 99%
“…The presence of fluorides in the electrolyte causes the chemical dissolution of the titanium oxide to form the water-soluble [TiF 6 ] −2 complex. On the other hand, the complex also occurs with the Ti 4+ ions that are ejected at the interface of oxide-electrolyte by the following overall reactions [20][21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…The XPS signal in the F 1s binding energy region consisted of only one band, peaking around 684 eV, due to surface fluoride ions. 30,38 No XPS signal at 688 eV, assigned to substitutional ions in the F-TiO 2 lattice, could ever be detected, possibly always being below the detection limit of the XPS technique. The effective dopant/Ti molar ratio determined by quantitative XPS analysis, also reported in Table 1, was usually lower than the nominal value according to the synthesis of the different doped TiO 2 series.…”
Section: Photocatalysts Structurementioning
confidence: 99%
“…Anion doping with p-block elements has been successfully pursued to sensitize TiO 2 towards visible light, 4,5 either by introducing newly created mid-gap energy states, or by narrowing the band gap itself. The effectiveness, but also the still not completely well understood nature of doping titanium dioxide with main group elements, such as N, 4,6-13 C, 5,14-17 B, [18][19][20] S, 13,15,[21][22][23][24][25] P, 26,27 I, 28,29 and F, [30][31][32][33][34][35][36][37][38][39] have been ascertained in a great number of studies, which also demonstrated that the insertion of dopant impurities in the oxide structure may increase the rate of undesired recombination of the photogenerated charge carriers. In contrast, the latter effect is known to become relatively lower, the higher is the crystallinity degree of the oxide structure.…”
Section: Introductionmentioning
confidence: 99%